Cooperative Recruitment of FtsW to the Division Site of Bacillus subtilis - Gamba, Pamela; Hamoen, Leendert W.; Daniel, Richard A. (Frontiers in Microbiology, 2016)
Five essential proteins are known to assemble at the division site of Bacillus subtilis. However, the recruitment of the FtsW homolog is still unclear. Here, we take advantage of spore germination to facilitate the depletion of essential proteins and to study the divisome assembly in the absence of previous division events. We show that, unlike what has been shown for the Escherichia coli divisome, the assembly of FtsW is interdependent with the localization of PBP 2B and FtsL, which are key components of the membrane bound division complex. Interestingly, the Z-ring appeared to disassemble upon prolonged depletion of late division proteins. Nevertheless, we could restore Z-ring formation and constriction by re-inducing FtsW, which suggests that the stability of the Z-ring is stimulated by the assembly of a functional division complex.